DAMPAK INTERPRETASI TEKSTUAL DAN KONTEKSTUAL TERHADAP HADIST KEPEMIMPINAN WANITA - Ghaffar, Abd (Fakultas Agama Islam Universitas Islam Madura, 2019)
The hadith's interpretation of women's leadership since classics and now there are differences of opinion among scholars. Some scholars tend to allow women to be leaders in strategic positions, while some other scholars tend not to allow women to be leaders. Their views on whether or not women can become leaders are supported by each of the arguments they build, both textual and contextual interpretations. When the hadith is examined and interpreted textually, it will produce a conclusion that a woman should not be a leader in various situations and conditions and any reasons. However, if the argument they build is analyzed contextually, then it seems a more logical and rational view. The scholars who allow women to be leaders with consideration of the benefits and interpretations that will cause it. With this contextual interpretation, women's leadership in all walks of life of society, nation and state